Identifikasi dan Uji Sensitivitas Staphylococcus sp. Terhadap Beberapa Antibiotik pada Ulkus Diabetikum - Septiana Septiana; Ajeng Viona Putri Anjarani; Didik Wahyudi (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Staphylococcus sp bacteria can cause infection in diabetic ulcers. Treatment of infections can use antibiotics, but the use of antibiotics can have negative impacts such as bacterial resistance to antibiotics. The aim of this research is to determine the results of identifying the bacteria Staphylococcus sp. (Staphylococcus aureus and Staphylococcus epidermidis) in diabetic ulcers and bacterial sensitivity to the antibiotics gentamicin, clindamycin, chloramphenicol and ciprofloxacin. The research design in this study used descriptive observational. The samples in this study were taken by accidental sampling in the period November to December 2023, resulting in 10 samples. Bacterial identification was carried out using biochemical test methods and sensitivity tests using the Kirby-Bauer method. The results of the bacterial identification research found Staphylococcus aureus bacteria in 7 out of 10 samples and Staphylococcus epidermidis bacteria in 3 out of 10 samples. The results of the sensitivity test concluded that the bacteria Staphylococcus sp. sensitive to the antibiotics gentamicin by 70%, clindamycin by 50%, chloramphenicol by 70% and ciprofloxacin by 70%.